THE INFLUENCE OF PERSONAL PROTECTIVE EQUIPMENT (PPE) USE AND PERIOD OF WORK ON THE INCIDENT OF PERSONAL PROTECTIVE EQUIPMENT (ARI) AMONG LANDFILL - Yordayumike Tafuli; Frida Fallo; Maria Magdalena Gabriella Bale (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Acute Respiratory Infection (ARI) is one of the most common health problems among informal workers, including waste pickers who are exposed to dust, bioaerosols, and hazardous gases at landfill sites. This study aimed to analyze the association between working duration and the use of personal protective equipment (PPE) with the incidence of ARI among waste pickers at Alak Landfill, Kupang City. This analytical quantitative study employed a cross-sectional design involving 90 respondents selected using a total sampling technique. Data were collected using a structured questionnaire and analyzed using the Chi-square test. The results showed that 87 respondents (96.7%) experienced ARI. There was a significant association between working duration and ARI incidence (p=0.003), in which all respondents with a working duration of more than five years experienced ARI (73.3%). In addition, PPE use was significantly associated with ARI incidence (p0.001), all respondents who did not use PPE experienced ARI (84.4%). In conclusion, working duration and PPE use were significantly associated with ARI incidence among waste pickers at Alak Landfill, Kupang City.